A Study and Implementation of Music Editor Application for Android Mobile Phone - Eka, Wijaya (2010)
Literature review is the first chapter of whole document of this project. This chapter discusses about the finding materials related to the project. The author will discuss about embedded system, mobile computing, mobile phone, mobile platform and music editor application. This chapter will be broken down into several subsections which contain discussion about those topics mentioned by the author.